Evidence of neglect of the elderly in sub-Saharan Africa: a scoping review protocol - Mustapha Amoadu; Amidu Alhassan; Irene Korkoi Aboh; Frank Offei Odonkor Offei; William Akoto-Buabeng (BMJ Open)
Introduction The elderly constitute a significant demographic in society, relying on social and healthcare support of its country. However, despite their vulnerability and dependence, instances of negligence within sub-Saharan Africa (SSA) towards this demographic have been reported anecdotally, yet remain poorly understood and documented. The purpose of this protocol is to outline the systematic approach to investigating the neglect of the elderly population in SSA. The elderly population are the point of focus but they will not be directly involved but through secondary data.Methods and analysis Search will be condcuted in Ovid MEDLINE, PubMed, CINAHL, Embase, Web of Science, Cochrane Library, grey literature, professional society websites and the International Clinical Trials Registry Platform. Only qualitative study designs, clinical practice guidelines, policy documents and professional society recommendations relevant to study objective will be used. The time lapse for this study will be from January 2000 and later. Two authors will independently perform data extraction in duplicate and complete risk of bias and quality assessment using recommended tools. Study appraisal will be conducted using the Joanna Briggs Institute (JBI) critical appraisal tool for qualitative studies.Trial registration https://doi.org/10.17605/OSF.IO/PK2VJ.Ethics and dissemination This study does not involve patients and animals; therefore, written informed consent will not be required. The findings from the study will be disseminated to stakeholders such as the Ministry of Health, policy implementers at local government level and chiefs for discussion and implementation of the findings. It will also be presented at conferences for the consumption of the global world.